Ibn Ḥazm of Cordoba : the life and works of a controversial thinker - Adang, Camilla.; Fierro, Ma. Isabel; Schmidtke, Sabine. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2013)
This volume represents the state of the art in research on the controversial Muslim legal scholar, theologian and man of letters Ibn Ḥazm of Cordoba (d. 456/1064), who is widely regarded as one of the most brilliant minds of Islamic Spain. Remembered mostly for his charming treatise on love, he was first and foremost a fierce polemicist who was much criticized for his idiosyncratic views and his abrasive language. Insisting that the sacred sources of Islam are to be understood in their outward sense and that it is only the Prophet Muḥammad whose example may be followed, Ibn Ḥazm alienated himself from his peers. As a result, his books were burned and he was forced to withdraw from public life. Contributors are: Camilla Adang, Hassan Ansari, Samuel-Martin Behloul, Alfonso Carmona, Leigh Chipman, Maribel Fierro, Alejandro García Sanjuán, Livnat Holtzman, Samir Kaddouri, Joep Lameer, Christian Lange, Gabriel Martinez Gros, Luis Molina, Salvador Peña, Jose Miguel Puerta Vilchez, Rafael Ramón Guerrero, Adam Sabra, Sabine Schmidtke, Delfina Serrano, Bruna Soravia, Dominique Urvoy, Kees Versteegh and David Wasserstein.